Brown Adipose Tissue, Diet-Induced Thermogenesis, and Thermogenic Food Ingredients: From Mice to Men - Saito, Masayuki; Matsushita, Mami; Yoneshiro, Takeshi; Okamatsu-Ogura, Yuko (Frontiers in Endocrinology, 2020)
Since the recent rediscovery of brown adipose tissue (BAT) in adult humans, this thermogenic tissue has been attracting increasing interest. The inverse relationship between BAT activity and body fatness suggests that BAT, because of its energy dissipating activity, is protective against body fat accumulation. Cold exposure activates and recruits BAT, resulting in increased energy expenditure and decreased body fatness. The stimulatory effects of cold exposure are mediated through transient receptor potential (TRP) channels and the sympathetic nervous system (SNS). Most TRP members also function as chemesthetic receptors for various food ingredients, and indeed, agonists of TRP vanilloid 1 such as capsaicin and its analog capsinoids mimic the effects of cold exposure to decrease body fatness through the activation and recruitment of BAT. The antiobesity effect of other food ingredients including tea catechins may be attributable, at least in part, to the activation of the TRP–SNS–BAT axis. BAT is also involved in the facultative thermogenesis induced by meal intake, referred to as diet-induced thermogenesis (DIT), which is a significant component of the total energy expenditure in our daily lives. Emerging evidence suggests a crucial role for the SNS in BAT-associated DIT, particularly during the early phase, but several gut-derived humoral factors may also participate in meal-induced BAT activation. One intriguing factor is bile acids, which activate BAT directly through Takeda G-protein receptor 5 (TGR5) in brown adipocytes. Given the apparent beneficial effects of some TRP agonists and bile acids on whole-body substrate and energy metabolism, the TRP/TGR5–BAT axis represents a promising target for combating obesity and related metabolic disorders in humans.